1992
DOI: 10.1007/bf01066794
|View full text |Cite
|
Sign up to set email alerts
|

Single-locus control of saccharin intake in BXD/Ty recombinant inbred (RI) mice: Some methodological implications for RI strain analysis

Abstract: The sac locus, with a major effect on saccharin preference, was discovered by Fuller (1974) in C57BL/6J (B6), DBA/2J (D2), and derived crosses, and is now supported in the BXD/Ty recombinant inbred (RI) series by a marked bimodal distribution in saccharin preference among 20 strains. The B6 allele led to increased saccharin preference compared to the D2 allele. Since the search for bimodal distributions reflecting major gene loci is an essential part of RI strain analysis, a new statistical method is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…In 1974, using long-term two-bottle tests, Fuller (60) showed that differences in saccharin preferences between the C57BL/6 and DBA/2 inbred strains largely depend on a single locus, Sac, with a dominant Sac b allele present in the C57BL/6 strain that was associated with higher saccharin preference and a recessive Sac d allele present in the DBA/2 strain that was associated with lower saccharin preference. Subsequent studies confirmed this finding in the BXD recombinant inbred strains, and in crosses between the C57BL/6 and DBA/2 and between the C57BL/6 and 129 strains (16,23,26,113,115,133). In addition to sweetener preferences, the Sac genotype influenced the afferent responses of gustatory nerves to sweeteners (16,98), which indicated that the Sac gene is involved in peripheral taste transduction and may encode a sweet taste receptor.…”
Section: T1r Receptors Discoverysupporting
confidence: 62%
“…In 1974, using long-term two-bottle tests, Fuller (60) showed that differences in saccharin preferences between the C57BL/6 and DBA/2 inbred strains largely depend on a single locus, Sac, with a dominant Sac b allele present in the C57BL/6 strain that was associated with higher saccharin preference and a recessive Sac d allele present in the DBA/2 strain that was associated with lower saccharin preference. Subsequent studies confirmed this finding in the BXD recombinant inbred strains, and in crosses between the C57BL/6 and DBA/2 and between the C57BL/6 and 129 strains (16,23,26,113,115,133). In addition to sweetener preferences, the Sac genotype influenced the afferent responses of gustatory nerves to sweeteners (16,98), which indicated that the Sac gene is involved in peripheral taste transduction and may encode a sweet taste receptor.…”
Section: T1r Receptors Discoverysupporting
confidence: 62%
“…Fuller (1974) demonstrated that most of the differences in saccharin preferences between C57BL/6J and DBA/2J strains depend on a single locus, Sac, with the dominant Sac b allele present in the C57BL/6J strain. Subsequent studies confirmed this finding in the BXD recombinant inbred strains, in crosses between the C57BL/6 and DBA/2 strains (Lush, 1989;Belknap et al, 1992;Phillips et al, 1994;Lush et al, 1995;Blizard et al, 1999) and in crosses between the C57BL/6ByJ and 129P3/J strains (Bachmanov et al, 1997). The Sac locus has been mapped to the subtelomeric region of mouse chromosome 4 (Phillips et al, 1994;Lush et al, 1995;Bachmanov et al, 1997;Blizard et al, 1999;Li et al, 2001) and more recently has been cloned positionally .…”
Section: Introductionsupporting
confidence: 58%
“…Although there still may have been interactions between solutions tested in this study, it seems unlikely that they would be sufficiently robust to affect the main conclusions about the direction of strain differences between B6 and 129 strains. Indeed, in our other experiments on these strains, 9,20,30 as well as in studies by other authors, 5,8,[10][11][12]15 B6 and 129 mice had the same character of differences in ethanol, sucrose, saccharin, citric acid, quinine, and NaCl consumption, regardless of whether the solutions were tested in the same or in different groups of animals.…”
Section: Discussionmentioning
confidence: 81%
“…Although there still may have been interactions between solutions tested in this study, it seems unlikely that they would be sufficiently robust to affect the main conclusions about the direction of strain differences between B6 and 129 strains. Indeed, in our other experiments on these strains, 9,20,30 as well as in studies by other authors, 5,8,[10][11][12]15 B6 and 129 mice had the same character of differences in ethanol, sucrose, saccharin, citric acid, quinine, and NaCl consumption, regardless of whether the solutions were tested in the same or in different groups of animals.To summarize, the higher ethanol consumption of B6 mice relative to 129 mice is accompanied by higher preferences for sweet and sour, possible reduction in the aversion to bitter, no change in capsaicin sensitivity, and a lower preference for salty taste. These data are consistent with the hypothesis that the higher ethanol intake by B6 mice depends, in part, on higher hedonic attractiveness of its sweet taste component.…”
mentioning
confidence: 81%